The association between dietary fiber intake with blood glucose and lipid profile among older adult with possible sarcopenia and sarcopenia in Kelantan - Isharuddin, Lydia (Universiti Sains Malaysia, 2024)
Sarcopenia is an age-related disease characterized by the loss of muscle mass and strength. This study aimed to determine the association between dietary fiber intake and blood glucose and lipid profiles among older adults with possible sarcopenia and sarcopenia in Kelantan. This crosssectional study involved 92 older adults aged 60 and above, residing independently in the community. Participants were recruited through convenience sampling. Dietary fiber intake was assessed using the Diet History Questionnaire (DHQ), and blood samples were collected after an overnight fast to analyze glucose levels and lipid profiles, including total cholesterol (TC), highdensity lipoprotein (HDL), low-density lipoprotein (LDL), and triglycerides (TG). Sociodemographic and medical history characteristics were also collected during interviews. Sarcopenia was screened using cut-off points from the Asian Working Group of Sarcopenia (AWGS), and skeletal muscle index (SMI) was determined using body impedance analysis (BIA). Dominant handgrip strength was measured with a Jamar dynamometer, and muscle performance was assessed using the short physical performance battery (SPPB). The findings revealed notably low dietary fiber intake, with median intakes of 3.54 grams for men and 3.29 grams for women. Median fasting blood glucose (FBG) levels were 5.60 mmol/L for men and 5.30 mmol/L for women, both within normal ranges. Both men and women demonstrated normal levels of triglycerides (TG) and high-density lipoprotein (HDL), but elevated levels of total cholesterol (TC) and low-density lipoprotein (LDL). Despite the low dietary fiber intake and notable blood glucose and lipid profiles, no significant relationship was found between fiber intake and blood glucose or lipid profiles in the studied population. Further research is needed to explore other factors that may influence these health parameters in older adults with sarcopenia.